2022
DOI: 10.3390/healthcare10102045
|View full text |Cite
|
Sign up to set email alerts
|

Examining Cognitive Factors for Alzheimer’s Disease Progression Using Computational Intelligence

Abstract: Prognosis of Alzheimer’s disease (AD) progression has been recognized as a challenging problem due to the massive numbers of cognitive, and pathological features recorded for patients and controls. While there have been many studies investigated the diagnosis of dementia using pathological characteristics, predicting the advancement of the disease using cognitive elements has not been heavily studied particularly using technologies like artificial intelligence and machine learning. This research aims at evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Based on this comparison, one’s most recent cognitive functioning can be evaluated ( Grossman et al, 1996 ; Hansen et al, 2018 ; Dunne et al, 2021 ). Nonetheless, despite being considered cost-effective and straightforward to administer, cognitive function tests are not sufficiently sensitive to identify the progression of MCI (for example, ADAS-Cog may be less responsive to change when used in people with MCI; Skinner et al, 2012 ; Thabtah et al, 2022b ). Notably, as writing and drawing are required in some tests, motor impairments such as post-stroke paralysis (frequently observed in patients with dementia) can lead to lower scores and inaccurate diagnoses ( Palsetia et al, 2018 ; Heyrani et al, 2022 ).…”
Section: “Ruling Out” Approach: the Challenge Of An Early And Accurat...mentioning
confidence: 99%
“…Based on this comparison, one’s most recent cognitive functioning can be evaluated ( Grossman et al, 1996 ; Hansen et al, 2018 ; Dunne et al, 2021 ). Nonetheless, despite being considered cost-effective and straightforward to administer, cognitive function tests are not sufficiently sensitive to identify the progression of MCI (for example, ADAS-Cog may be less responsive to change when used in people with MCI; Skinner et al, 2012 ; Thabtah et al, 2022b ). Notably, as writing and drawing are required in some tests, motor impairments such as post-stroke paralysis (frequently observed in patients with dementia) can lead to lower scores and inaccurate diagnoses ( Palsetia et al, 2018 ; Heyrani et al, 2022 ).…”
Section: “Ruling Out” Approach: the Challenge Of An Early And Accurat...mentioning
confidence: 99%
“…The results were promising in which processing only three cognitive elements by the classi cation algorithms, particularly C4.5, revealed high predictive classi cation models. Overall, the results of Thabtah et al (2022a;b) showed that cognitive elements are more impactful in regards to dementia progression than functional activities, at least with the data and methods considered. However, the studies by Thabtah et al 2018) determined that the ability of ADAS-Cog-13 to identify disease progression was better than that of ADAS-Cog-11, subsequently pinpointing the various versions of ADAS-Cog assessment available making it di cult for cross-comparison of validity and reliability.…”
Section: Thabtah Et Al (2022a) Expanded Functional Assessment Into As...mentioning
confidence: 93%
“…While pathological assessments of Alzheimer's disease (AD) diagnosis, such as using biological markers (biomarkers), and magnetic resonance imaging (MRI) [5] can be used to predict the disease, they are also time-and cost-intensive, stressful, and provide results requiring laboratory study and professional personnel who may not be available [6][7][8]. Therefore, cognitive assessments used for prodromal dementia such as the Alzheimer's Disease Assessment Scale-Cognitive 13 (ADAS-Cog-13), Mini Mental State Examination (MMSE), and others [9,10] are useful since they can screen for signs of early impairment.…”
Section: Introductionmentioning
confidence: 99%
“…However, identifying a few cognitive items that can be signs of the progression of the disease and can assist in early intervention is still a challenge [12]. Additionally, very few research studies have measured the progression of dementia using cognitive features with a data drive methodology, i.e., [6,8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation